Sutton Naevi as Melanoma Simulators: Can Confocal Microscopy Help in the Diagnosis? - Albert Brugués (Acta Dermato-Venereologica, 2020)

(untitled)
Sutton naevi can sometimes present a challenging appearance with atypical presentation, also by dermoscopy. Reﬂectance confocal microscopy could help in making a diagnosis. This study prospectively collected two groups of Sutton nevi: the first one was composed by typical white halo naevi monitored for one year (13, 23%) and the second one was made up of atypical lesions excised in order to rule out melanoma, which were histologically diagnosed as Sutton naevi (21, 37%). These two groups of Sutton naevi were compared to a retrospectively collected cohort of thin melanomas with histologic regression features (23, 40%). On dermoscopy, atypical Sutton naevi and melanomas were indistinguishable. Reﬂectance confocal microscopy demonstrated significant differences at the dermo-epidermal junction: marked dermo-epidermal junction thickening and non-edged papilla were associated with melanoma, while the presence of nests was associated with Sutton naevi. However, reﬂectance confocal microscopy also detected marked intraepidermal pagetoid cells in Sutton naevi that were a combination of MelanA+ and CD1a+ cells. Sutton naevi can simulate melanoma, under both dermoscopy and reﬂectance confocal microscopy. Nevertheless, relevant confocal dermo-epidermal junction features and the clinical scenario can be helpful to make a final diagnosis, especially in those situations where melanoma must be ruled out.